Catalyzed Gas Phase Ammoxidation of 2, 3 and 4-picolines - AL-Nuaimy, Rajiha I. (The Iraqi Journal of Veterinary Medicine, 2012)
Catalyst gas phase ammoxidation of 2,3, and 4- picolines in a fixed bed reactor is described the catalyst applied composed of Vanadium (V) and tin (Sn) Oxides supported on Al2O3 as described in recent papers (1), (2). The effect of NH3, O2, contact time and temperature of the picoline mole ratios on the yield and conversion of the products was studied. The conversationand yield are in the rate of 2-picoline> 4-picoline > 3-picoline.The applied catalyst was active even after 150 hours of reaction. The highest yield obtained of nicotinic acid was 90%, 88%, 87% 2-picoline, 4-picoline and 3-picoline respectively.